2021
DOI: 10.1108/jadee-07-2020-0145
|View full text |Cite
|
Sign up to set email alerts
|

Vertical coordination in the Chinese grape market

Abstract: PurposeRegarding the global development of the wine industry, China has gained a notable share in terms of wine consumption, and its domestic wine production has increased steadily since 2000. The wine production process requires close coordination between growers and processors to avoid disruption and instability in the supply chain of the wine grapes. However, vertical coordination in the Chinese wine regions has received little attention. Based on the existing theoretical background on vertical coordination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…To fill this gap, we investigate in the case study based on the example of China's largest wine producer Changyu, how the structure of DHEs in the Chinese wine business looks like and which mechanisms the leading enterprise applies to coordinate the internal structure and steps of production, processing and marketing. Bitsch et al (2021) have also found that differences between wine-growing regions might exist due to natural conditions. In Ningxia, for example, there is a water shortage, and vines have to be buried in winter (also see: Hao et al, 2015).…”
Section: Jadee 132mentioning
confidence: 98%
See 3 more Smart Citations
“…To fill this gap, we investigate in the case study based on the example of China's largest wine producer Changyu, how the structure of DHEs in the Chinese wine business looks like and which mechanisms the leading enterprise applies to coordinate the internal structure and steps of production, processing and marketing. Bitsch et al (2021) have also found that differences between wine-growing regions might exist due to natural conditions. In Ningxia, for example, there is a water shortage, and vines have to be buried in winter (also see: Hao et al, 2015).…”
Section: Jadee 132mentioning
confidence: 98%
“…So far, scholars have mainly focussed their research on DHEs in Chinese agriculture, horticulture and animal production. Regarding DHEs in the field of the wine business, not much research has been done to this point (Li et al , 2021; Bitsch et al , 2021; Rozelle et al , 2006). To fill this gap, we investigate in the case study based on the example of China's largest wine producer Changyu, how the structure of DHEs in the Chinese wine business looks like and which mechanisms the leading enterprise applies to coordinate the internal structure and steps of production, processing and marketing.…”
Section: Concept Of Dragon Head Enterprises – a Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, there is a need to consider the potential of China’s domestic wine consumption and production to satisfy domestic demand, as well as to increase its competitiveness in the international markets. One of its consequences is a shift from quantity to quality in production, which increases the value of Chinese wines (Bitsch et al , 2021). Wine consumption is expected to grow in line with the increasing income of Chinese consumers (Liu and Song, 2021).…”
Section: Introductionmentioning
confidence: 99%